Effects of dietary energy density and lysine:calorie ratio on the growth performance of growing pigs and subsequent finishing performance - Smith, J.W.II; O'Quinn, P.R.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty crossbred gilts were used in a growth trial to evaluate the effects of increasing dietary energy density and lysine:calorie ratio on growing pig growth performance and subsequent finishing performance. Feeding 3% choice white grease and 3.45 g lysine:Mcal ME maximized growth performance of growing gilts. Choice white grease additions and increasing lysine:calorie ratio during growing (65 to 160 lb) did not affect carcass back fat or loin depth at 235 lb.
Keywords: Swine; Feed:gain ratio; Energy density; Lysine:calorie ratio; Growing-finishing pigs